Social robotics : 8th International Conference, ICSR 2016, Kansas City, MO, USA, November 1-3, 2016 Proceedings /: 8th International Conference, ICSR 2016, Kansas City, MO, USA, November 1-3, 2016 Proceedings. (2016) - Unknown
No abstract available